Searching for dark matter signals from local dwarf spheroidal galaxies at low radio frequencies in the GLEAM survey. Issue 1 (17th March 2020) - Cook, R H W; Seymour, N; Spekkens, K; Hurley-Walker, N; Hancock, P J; Bell, M E; Callingham, J R; For, B-Q; Franzen, T M O; Gaensler, B M; Hindson, L; Johnston-Hollitt, M; et al.
ABSTRACT: The search for emission from weakly interacting massive particle (WIMP) dark matter annihilation and decay has become a multipronged area of research not only targeting a diverse selection of astrophysical objects, but also taking advantage of the entire electromagnetic spectrum. The decay of WIMP particles into standard model particles has been suggested as a possible channel for synchrotron emission to be detected at low radio frequencies. Here, we present the stacking analysis of a sample of 33 dwarf spheroidal (dSph) galaxies with low-frequency (72–231 MHz) radio images from the GaLactic and Extragalactic All-sky Murchison Widefield Array (GLEAM) survey. We produce radial surface brightness profiles of images centred upon each dSph galaxy with background radio sources masked. We remove 10 fields from the stacking due to contamination from either poorly subtracted, bright radio sources or strong background gradients across the field. The remaining 23 dSph galaxies are stacked in an attempt to obtain a statistical detection of any WIMP-induced synchrotron emission in these systems. We find that the stacked radial brightness profile does not exhibit a statistically significant detection above the 95 per cent confidence level of ∼1.5 mJy beam −1 . This novel technique shows the potential of using low-frequency radio images to constrain fundamental properties of particle dark matter.